ADVANTAGES OF BLOCKING INTRAMEDULLARY OSTEOSYNTHESIS IN TREATMENT OF PATIENTS WITH FRACTURES OF THE FOREARM BONES - V. A. Neverov; S. N. Chernyaev (Вестник хирургии имени И.И. Грекова, 2018)
The blocking intramedullary osteosynthesis (BIO) of the forearm bones possesses quite a number of advantages in comparison with the bone and transosseous methods. The BIO allows the restoration of the anatomy and biomechanics of the forearm, it shortens the term of disability and restores the function of the extremity in proximate terms. The BIO of the forearm bones consists of great number of nuances, each of them is really important. It is necessary to have the X-ray unit with electron-optical image for the intraoperative monitoring of operation stages and to follow the well-defined algorithm of technology of performing BIO of the forearm bones with special reference to all possible features of anatomy.